Evaluating the ancillary services market for large-scale renewable energy integration in China's northeastern power grid. (April 2021) - Hu, Junfeng; Yan, Qingyou; Kahrl, Fredrich; Liu, Xu; Wang, Peng; Lin, Jiang
Abstract: The installed renewable energy capacity in China is the largest in the world. However, the curtailment of renewable energy remains problematic. To alleviate this problem, a pilot for integrating the ancillary service market for renewable energy in China's northeastern power grid began in 2017. Before this time, a compensatory ancillary service cost mechanism was implemented, in which thermal plants not providing ancillary service paid the costs of the thermal plants providing ancillary service under government supervision. The pilot ancillary service market allowed thermal plants providing ancillary service to make independent quotes. Renewable energy plants were included in those paying the ancillary service costs. We examine the effects of the ancillary service market in the context of large-scale renewable energy integration. The results show that this market has given rise to competing interests between renewable energy and thermal plants. Therefore, measures must be taken to improve the ancillary service market, including eliminating the ancillary service bidding limits, establishing a renewable auction mechanism, and transforming the spot market. Highlights: The ancillary services market for renewable in Northeastern China grid should be improved. The ancillary services costs would increase with more and more wind generation share. The renewable ancillary services demand bidding mechanism should be created. The ancillary service costs should be borne by the demand load and renewable energy.